Autism and Religion - Szabolcs Kéri (MDPI AG, 2023)
The disease burden of autism spectrum disorder (ASD) is a definitive public health challenge. The quality of life of children with ASD depends on how the cultural environment fits their special needs, including religious and spiritual factors. Does ASD predict low religiosity, and if not, what is the significance for clinical care? To answer this question, we reviewed the literature on the cognitive models of ASD and religious beliefs. We found that the cognitive models of ASD and religious beliefs substantially overlap, which is particularly important from a developmental psychological perspective. These models include Theory of Mind and intentionality, the "broken mirror" hypothesis, central coherence, and the intense world theory. We dispute the assumption that individuals with ASD are inherently less religious and spiritual than the neurotypical population. Religiosity is possibly expressed differently in ASD with unique spiritual experiences and beliefs ("gifted, visionary, and truth-seeker"). In some circumstances, a religious background can be helpful for both children with ASD and their caregivers. These circumstances should not be neglected, and clinicians are encouraged to consider patients' religious context, resources, and needs.